Problematika Guru PAI dalam Membina Perilaku Sosial Siswa - Ahmad Shofiyuddin (Darajat: Jurnal Pendidikan Agama Islam, 2019)
This article aims to find out the process of fostering social behavior of students, how to know the problems experienced by PAI teachers and to find out efforts in overcoming the problems experienced by PAI teachers in Jadid Ar-Rohman Middle School Sendangharjo. While the approach used in this study is a qualitative approach, namely an approach that emphasizes more on the analysis of deductive and inductive inference processes, and on the analysis of the dynamics of the relationship between observed phenomena, using scientific logic. PAI Teacher Problems in improving students' social behavior; Lack of interest and awareness of students in carrying out school discipline, Lack of development of school facilities and infrastructure, poor social environment, so that there are some of the students whose behavior is not good. Efforts to overcome the problems experienced by PAI teachers in Jadid Ar-Rohman Middle School Sendangharjo Brondong Lamongan Indonesia include; Building positive social behavior habits, Complete lack of facilities and infrastructure, Building exemplary, Establishing communication with various parties.